A closer look at the sources of variability in scalar implicature derivation: a review - Khorsheed, Ahmed; Gotzner, Nicole (Frontiers in Communication, 2023)
For more than twenty years now, studies in experimental pragmatics have provided invaluable insights into the cognitive processes involved in deriving scalar implicatures and achieving inferential comprehension. However, these studies have always reported a notable degree of variability that remained inadequately discussed in the literature. For instance, upon closer inspection of the reports, one can always find a group of individuals who tend to be largely pragmatic, overwhelmingly logical, and sometimes mixed not showing a clear preference. There also exist newly-devised paradigms that prompt a radically different type of response than other paradigms, and thus new evidence casting doubt on long-established findings in the field. More recent reports on scalar diversity further suggest that differences in the semantic structure of scalar words can lead to differing rates of scalar implicatures and influence the time invested in pragmatic processing. Indeed, one can contend that the current empirical landscape on scalar implicatures can be characterized as having three primary sources of variability: inter-individual, methodological, and linguistic. What factor or factors are behind these patterns of variability, and how can we interpret them in light of a pragmatic theory? This paper has a twofold objective: one is to review the previous experimental record on scalar implicatures from variability-based lenses, and the other to discuss the factor(s) that could account for this observed variability in the literature. Avenues for future research are provided.